С.В.Бородаєвський - професор кооперації українських еміграційних вищих навчальних закладів - Глушан, О.В. (Сумський історико-архівний журнал, 2010)
There is considered the pedagogical activity of the Ukrainian scientist S.V.Borodaevsky in the higher educational institutions created by the Ukrainian emigration in Czecho-Slovak Republic in the 20-30ies of the XX century, in particular there is analyzed his contribution to the organization and development of the higher co-operative education in the Ukrainian economic academy.